Redesigning Financial Mechanics and Constructive Political Finance in Iraq: A Serious Vision for the Future (International Journal of Financial, Administrative and Economic Sciences, 2024)
Fiscal policy in oil-dependent economies tends to follow oil price trends at the expense of efficiency and effectiveness, weakening the flexibility of fiscal policy tools to respond to the requirements of economic development and to achieve goals of stability, justice, and well-being. The decline in crude oil prices in 2014 provided an opportunity for most oil-producing countries, including Iraq, to address and mitigate the effects of an unjustified reliance on oil to finance the budget and sectors of the national economy. Similarly, the events of the COVID-19 pandemic in 2019 prompted the world to reconsider its economic strategies. This research aims to clarify the issues within Iraq's financial policy and propose solutions by developing a new fiscal policy design based on an ambitious, adaptable future vision.
Keywords: Fiscal Policy; National Economy; Oil Producing; Political Finance